Financial frictions and firm dynamics - Gomes, Germano Wallerstein Ferreira (2020)
Developing countries often lack medium and large firms, having a firm size distribution skewed towards smaller firms. This paper focuses on the impact of financial frictions in shaping these firm size distributions. To do so, I modify a continuous time model of firm entry and exit, based on the seminal contribution of Hopenhayn (1992), introducing two financial frictions. I also perform counterfactual analysis of different credit market reforms, analyzing both their aggregate impacts and their consequences across the firm size distribution, shedding light on the distributional impacts of these reforms.